Internal Fixation of Unstable Osteochondritis Dissecans in the Skeletally Mature Knee with Metal Screws. (April 2016) - Barrett, Ian; King, Alexander H.; Riester, Scott; van Wijnen, Andre; Levy, Bruce A.; Stuart, Michael J.; Krych, Aaron J.
Purpose: Several bioabsorbable and metal options are available for internal fixation of an unstable osteochondritis dissecans (OCD) lesion, but currently there are little data on outcomes with metal headless compression screws in the adult knee. The purpose of this study was to determine (1) the radiographic healing rates, (2) midterm clinical outcomes, and (3) comparison between healed and unhealed OCD fragments after use of headless metal compression screws for the treatment of unstable OCD lesions in the knees of skeletally mature patients. Methods: Retrospective chart review for all skeletally mature patients who presented with unstable femoral condyle OCD lesions of the knee was conducted. All patients underwent open or arthroscopic reduction and internal fixation using headless metal compression screws. Preoperative and postoperative radiographs were reviewed with healing defined as radiographic evidence of union of the OCD progeny fragment with the condyle. Clinical outcome data were collected retrospectively using 3 validated outcome scores: International Knee Documentation Committee (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS), and Marx. Results: Twenty-two knees in 22 patients with a mean age of 21 years (range= 14-37 years) were followed for an average of 8.7 years (range = 2-22 years). Metal, headless, cannulated compression screws were used in all 22 cases. At a mean of 31 months postoperatively (range = 2-262), fragment union was observed in 18 knees (82%). The remaining 4 knees (18%) required loose fragment excision and hardware removal at a mean of 9 months (range = 2-16 months) postoperatively. Mean postoperative Marx score was 7 (range = 0-16), the mean postoperative IKDC score was 85 (range = 62-100), and mean KOOS scores included KOOS Pain (93; range = 69-100), KOOS Symptoms (86; range = 71-100), KOOS ADL (98; range = 90-100), KOOS Sports (82; range = 50-100), and KOOS QOL (76; range = 50-100). Conclusion: Headless metal compression screws provide a satisfactory union rate for treatment of unstable OCD lesions of the femoral condyles in skeletally mature patients. Patients achieving union have good knee function, maintain satisfactory activity levels, and have superior knee outcomes compared with those that failed to heal after fixation at mid to long-term follow-up.